2017
DOI: 10.1093/nar/gkw1295
|View full text |Cite
|
Sign up to set email alerts
|

Alternative lengthening of telomeres can be maintained by preferential elongation of lagging strands

Abstract: Alternative lengthening of telomeres (ALT) is a telomerase independent telomere maintenance mechanism that occurs in ∼15% of cancers. The potential mechanism of ALT is homology-directed telomere synthesis, but molecular mechanisms of how ALT maintains telomere length in human cancer is poorly understood. Here, we generated TERC (telomerase RNA) gene knockouts in telomerase positive cell lines that resulted in long-term surviving clones acquiring the ALT pathway but at a very low frequency. By comparing these A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 57 publications
(90 reference statements)
3
47
0
Order By: Relevance
“…Moreover, in mice, ATRX has been shown to reduce HP1α and lead to chromatin decompaction [66]. Finally, a recent study has shown that preferential elongation of overhangs at the lagging chromatids promotes ALT, and ATRX was shown to partially suppress this process [69]. Despite the frequent mutation rate of ATRX/DAXX, its worth to mention that their mutations alone are not enough to initiate ALT, as has been shown for SV-40 hTERT immortalized cell lines [44].…”
Section: The Role Of Atrx and Daxxmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, in mice, ATRX has been shown to reduce HP1α and lead to chromatin decompaction [66]. Finally, a recent study has shown that preferential elongation of overhangs at the lagging chromatids promotes ALT, and ATRX was shown to partially suppress this process [69]. Despite the frequent mutation rate of ATRX/DAXX, its worth to mention that their mutations alone are not enough to initiate ALT, as has been shown for SV-40 hTERT immortalized cell lines [44].…”
Section: The Role Of Atrx and Daxxmentioning
confidence: 96%
“…The violet branch involves factors that are associated with heterochromatic state or stability of telemetric DNA ends. While ATRX/DAXX genes are mutated in the majority of ALT cells, the depletion of wild variants also promotes ALT activity [69]. We did not have genome variant data for the studied samples, and thus have considered higher expressions of these genes to have inhibitory effects on ALT.…”
Section: The Alt Pathwaymentioning
confidence: 99%
“…ALT telomeres are highly heterogeneous in length, but the average length is about double that of most somatic cells where telomeres are maintained by telomerase [37]. ALT telomeres can also display excessively long single-strand G-rich overhangs, with the longest reported measuring 400 nucleotides [38], more than twice the reported overhang length in telomerase positive cells. There is also evidence that ALT positive cells possess highly unusual telomeric structures not found in telomerase positive cell lines.…”
Section: Phenotypes Specific To Altmentioning
confidence: 99%
“…Telomere maintenance in ALT is thought to be mediated by a pathway referred to as break induced replication (BIR), with a preference for lagging strand synthesis (57). Seminal work in the field from Dilley et al implicated a primary three protein axis of POLD3, PCNA, and RAD52 in the mechanism of ALT telomere extension.…”
Section: Break Induced Replication Drives Alt Telomere Synthesismentioning
confidence: 99%